2014
DOI: 10.18869/acadpub.jnms.1.3.62
|View full text |Cite
|
Sign up to set email alerts
|

The effects of premarital relationship enrichment programs on marriage strength: A narrative review article

Abstract: Background and Purpose: Strengthening marriage relationship includes a body of programs focusing on boosting the couples' common understanding, honesty, trust, empathy and coordination. Premarital consultation along with the couples' relationship enrichment can result in their improved relationship. The current study aims to analyze the studies conducted on consultation programs for marriage relationship enrichment and marriage strength. Methods:The current study is a narrative review performed using key words… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Most studies have referred to the age ranges of 18–25 and 24–30 years as suitable marriage ages for men and women, respectively (12–14) because some believe that marriage at these ages is accompanied with a higher quality of life and that marriage at the age of below 18 for women and 20 for men will likely be associated with divorce or failure (11) and decreased stability of marriage (15). In some studies, it was indicated that young and old married individuals were not satisfied with their married lives; however, dissatisfaction was higher among young married couples (16–17). It seems that the suitable marriage age is influenced by culture and geographical region (18).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies have referred to the age ranges of 18–25 and 24–30 years as suitable marriage ages for men and women, respectively (12–14) because some believe that marriage at these ages is accompanied with a higher quality of life and that marriage at the age of below 18 for women and 20 for men will likely be associated with divorce or failure (11) and decreased stability of marriage (15). In some studies, it was indicated that young and old married individuals were not satisfied with their married lives; however, dissatisfaction was higher among young married couples (16–17). It seems that the suitable marriage age is influenced by culture and geographical region (18).…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, it was indicated that young and old married individuals were not satisfied with their married lives; however, dissatisfaction was higher among young married couples (16–17). It seems that the suitable marriage age is influenced by culture and geographical region (18). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations